Trinidad and Tobago : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Trinidad and Tobago. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights a decline in the real GDP of Trinidad and Tobago of 6 percent in 2016, with a further decline of 3.25 percent projected by the IMF staff in 2017. The combined impact of weak growth and low energy sector revenues increased the overall fiscal deficit to 12.1 percent of GDP in fiscal year 2016, though it is expected to drop to 11.0 percent of GDP in fiscal year 2017. Meanwhile, the current account deteriorated by 14.5 percentage points to a deficit of 10.7 percent of GDP in 2016. The government has taken steps to adjust fiscal imbalances, through efforts to reform the energy tax regime, reduce fuel subsidies, and boost nonenergy revenues.